Chromosomal analysis of progenies between Lilium intersectional hybrids and wild species using ND-FISH and GISH - Zhou, Mei; Yong, Xue; Zhu, Jungang; Xu, Qian; Liu, Xiaodan; Zhang, Lu; Mou, Lisha; Zeng, Lijia; Wu, Mengxi; Jiang, Beibei; Jia, Yin; Zhang, Peihua; et al. (Frontiers in Plant Science, 2024)
Intersectional hybrids in lilies possess significant breeding value, however, the lack of complete lily genomes and complex genotypes pose challenges for early identification of lily hybrids. This study aimed to use intersectional hybrid cultivars as female parents and wild lilies as male parents to facilitate early identification of hybrid offsprings and enhance the efficiency and convenience of the process. The nature of the cross combinations using Non-denaturing Fluorescence In Situ Hybridization (ND-FISH) and Genomic In Situ Hybridization (GISH) techniques was investigated. Three novel oligonucleotide probes-Oligo-pTa794, Oligo-pITS and Oligo-telo-were developed for lily chromosome research. Our results demonstrated successful hybridization between wild lilies and intersectional hybrid cultivars, producing a total of 130 hybrid progenies. The combination of ND-FISH and GISH analyses effectively revealed the genomic composition of the hybrid progeny and determined the parental origin of specific chromosomes, enabling more precise, efficient, and convenient identification of hybrid offsprings. This research not only provides significant guidance for lily breeding practices but also offers a valuable reference for the application of ND-FISH and GISH techniques in interspecific hybridization breeding and molecular cytogenetic research across various plant species.